PENGARUH MOTIF CORPORATE SOCIAL RESPONSIBILITY TERHADAP KUALITAS LINGKUNGAN DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN DI INDONESIA - Ririn Breliastiti (Jurnal Akuntansi Bisnis, 2017)
CSR activities have become a major program for the majority of mining companies in Indonesia. Publications and research related to CSR activities have been carried out both by companies and researchers, but only few studies discussing the motives behind the CSR programs. This study aims to investigate the influence of CSR motives for CSR activities and their impact on financial performance. Research conducted on twelve mining companies listed on the Stock Exchange in 2009 - 2011. The data were obtained by using content analysist of the annual report of the company. Statistical tests conducted on the classical assumption test and regression test. The results obtained from this study is the motive of CSR has no effect on CSR activities  (environmental quality). CSR activities (environmental quality) does not affect the company's financial performance. Environmental quality are mediating for altruistic motives to CFP1 (TVA), and mediating for financial motives and ethic motives to CFP2 (ROA). Keywords: Corporate Social Responsibility, environmental quality, financial performance.